Ecological aspects of mesozooplankton in marine protected area of the tropical southwestern atlantic - Campelo, Renata Polyana de Santana (2019)
CAMPELO, Renata Polyana de Santana. BEZERRA, Luis Ernesto Arruda (orientador). LEITÃO, Sigrid Neumann (coorientadora). MELO JUNIOR, Mauro de (coorientador). Ecological aspects of mesozooplankton in protected marine area of the tropical southwestern atlantic. 2019. 171f.: Tese de doutorado em Ciências Marinhas Tropicais. Universidade Federal do Ceará. Instituto de Ciências do Mar. Programa de Pós-Graduação em Ciências Marinhas Tropicais. Fortaleza - CE. 2019.